Cancer Molecular Screening and Therapeutics (MoST): a framework for multiple, parallel signal‐seeking studies of targeted therapies for rare and neglected cancers. Issue 8 (27th August 2018) - Thavaneswaran, Subotheni; Sebastian, Lucille; Ballinger, Mandy; Best, Megan; Hess, Dominique; Lee, Chee K; Sjoquist, Katrin M; Hague, Wendy E; Butow, Phyllis N; Simes, R John; Thomas, David
Abstract: Background: Precision medicine aims to link molecular targets in tumours with corresponding therapies, particularly for patients with rare cancers. Innovative approaches are needed to translate molecular opportunities into clinical care. The Cancer Molecular Screening and Therapeutics (MoST) program employs a molecular screening platform to identify molecular changes of therapeutic relevance (actionable changes) and a master protocol for multiple, parallel signal‐seeking clinical substudies, focused on therapies for patients with rare and neglected cancers. Methods and analysis: Archival pathology laboratory samples from patients with treatment‐refractory advanced solid cancer of any histologic type undergo molecular tumour profiling. Following review by a Molecular Tumour Board, eligible patients are offered treatment in therapeutic substudies. This novel master protocol allows expedited addition of individual substudies; at least 12 open label, single arm, signal‐seeking substudies during the initial 4 years of MoST are planned. The primary objectives are to identify signals of efficacy for developing biomarker‐driven therapies and biomarkers that more accurately predict response to therapy, as well as to evaluate the MoST design. Ethics approval: The program has been approved by the St Vincent's Hospital Sydney Human Research Ethics Committee (reference, HREC/16/SVH/23). Dissemination of results: A report summarising and interpreting collected study data will be published. Our findings will be presented at national and international conferences and scientific meetings, and published in peer‐reviewed journals. Trial registration: Australia New Zealand Clinical Trials Registry: ACTRN12616000908437 (8 July 2016).